The Fall of Troy - Quintus, Smyrnaeus, active 4th century; Way, Arthur S. (Arthur Sanders), 1847-1930 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Fall of Troy" by Quintus of Smyrna is an epic poem written in the 3rd century AD. It continues the story of the Trojan War from where Homer's Iliad ends, spanning from Hector's death to Troy's final destruction. The narrative follows the arrival of the Amazon warrior Penthesileia, the tragic fate of Achilles, the bitter contest for his armor, and the cunning stratagem of the wooden horse that seals Troy's doom. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Posthomerica
Release date is 1996-09-01
Produced by Douglas B. Killings
Keywords: Epic poetry, Greek -- Translations into English; Trojan War -- Poetry; Troy (Extinct city) -- Poetry